1980
DOI: 10.1103/physrevlett.44.17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Collectivity on Target-Fragmentation Reactions

Abstract: A new approach based on the collective tube model is developed for understanding momentum transfer to target fragments in high-energy hadron-nucleus collisions. Collectivity manifests itself in an enhanced dependence of momentum transfer on projectile energy, consistent with experimental results for deep-spallation reactions. The effective target for 149 Tb production from 197 Au by high-energy protons is deduced to consist of 3.1 ± 0.4 nucleons. Extensions of this model to nucleus-nucleus collisions are discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…For the Au target such an effective target would have a mass of 3.6 nucleons, what fits well with estimated mass of the fireball of the present study and justifies identification of the "fireball" with the "effective target". Furthermore, the deep spallation process of production of 149 Tb, studied by Winsberg et al [14] in proton -Au collisions at energies 1 -300 GeV was also explained by Cumming [15] assuming manifestation of the effective target with the mass of (3.1 ± 0.4) nucleons for proton energies larger than ∼ 2 GeV. This mass again agrees with the "fireball" mass found in our investigations and confirms proposed interpretation of the "fireball".…”
Section: Discussionmentioning
confidence: 81%
“…For the Au target such an effective target would have a mass of 3.6 nucleons, what fits well with estimated mass of the fireball of the present study and justifies identification of the "fireball" with the "effective target". Furthermore, the deep spallation process of production of 149 Tb, studied by Winsberg et al [14] in proton -Au collisions at energies 1 -300 GeV was also explained by Cumming [15] assuming manifestation of the effective target with the mass of (3.1 ± 0.4) nucleons for proton energies larger than ∼ 2 GeV. This mass again agrees with the "fireball" mass found in our investigations and confirms proposed interpretation of the "fireball".…”
Section: Discussionmentioning
confidence: 81%
“…It was difficult to understand why such a simple model could successfully fit data for reactions which appeared to involve more conlplex interactions (22). However, recent work (23,24) has shown that eq. [I] with k = 1 can be derived as an approximation from a less restrictive single collision or multiple independent collision model involving small momentum and energy transfers in each step.…”
Section: Resultsmentioning
confidence: 99%
“…(b) In terms of the two-component EP-ET picture [23 l, the collision processes discussed in the present paper are gentle collisions, while those discussed by Cumming [34] are violent collisions. Note in particular that in the latter case, the energy transfer to the RT always increases with increasing bombarding energy and does not tend to a limiting value.…”
Section: Estimate Of Energy Transfer Due To Nuclear Frictionmentioning
confidence: 98%